PENGAYAAN MODUL BIOLOGI SMK PERTANIAN KONSEP PENGELOLAAN LIMBAH PENGGUNAAN SAMPAH ORGANIK DENGAN STARTER CAIRAN ISI RUMEN SAPI UNTUK BAHAN BAKU PEMBUATAN BIOGAS - Yandi, Edri Yandi; Wulandari, Sri Wulandari; Mahadi, Imam Mahadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The research was to determine utilization of organic waste with starter fluid cow rumen raw material for biogas production in March and May 2015. Results of the study are used to enrich the teaching materials in the form of biology modules vocational school Agriculture on the concept of waste management. This research was carried out by two phases: experimentation and enrichment modules. Research conducted experiments using completely randomized design (CRD) non factorial, which consists of 4 treatments and 3 replicates in order to obtain 12 experimental design. If there is a real test there will be a further test Duncans Multiple Range Test (DMRT) at 5%. The parameters observed biogas volume, the color of the flame, calor and power. Enrichment module is performed on the stage of analysis and design. The results showed that the use of organic waste with starter fluid cow rumen could potentially produce methane gas as a source of biogas. Treatment A (25% substrate: 75% starter) are best produce biogas with a biogas volume of 11.57 L, color blue flames, calorific value 5670 J and power 132.98 watts for 28 days of fermentation. The results could be used as an module enrichment for biological subjects Agriculture vocational school on the concept of waste management. Keywords: Module, Organic Waste, Fluid Cow Rumen, Biogas.